Method to determine the nadir PSA following partial gland ablation - Nelson N. Stone; Vassilios Skouteris; Rendi Shu; Richard G. Stock; Ben GL Vanneste (BJUI Compass)
Abstract Objectives The objective of this study is to propose a novel method of determining the nadir PSA (nPSA) for men with prostate cancer treated by partial gland ablation (PGA). Materials and Methods Two cohorts of men were analyzed to develop a formula for the nPSA in men undergoing PGA. First, 123 men with a suspicion of prostate cancer underwent transperineal mapping biopsy (TPMB) and found to have benign pathology. Their prostate‐specific antigen (PSA) was compared to the prostate volume using curve estimation regression analysis. Second, the contribution of PSA from an ablated region was determined by using a surrogate of 545 men who had whole‐gland brachytherapy followed by prostate biopsy. Biopsy results were compared to radiation dose (calculated as the biological equivalent dose) levels in men who were free from biochemical failure. The nPSA was then calculated by using the PSA density (PSAD) for the untreated volume plus the PSA from the post‐brachytherapy patients. Results The PSAD with the highest R2 (0.80, p < 0.001) for the 123 men who had TPMB and a negative biopsy was 0.12 ng/mL2. In the brachytherapy patients, five 20 Gy dose groups were analyzed from ≤140 to ≥220 Gy, which demonstrated a progressive decrease in the positive biopsy rate to 1.5% at the highest dose (p = 0.036). PSA was <0.2 ng/mL in 98.2% of these men. If brachytherapy was used for PGA and a dose of ≥ 220 Gy was delivered to the ablation zone, the nPSA could be calculated from the remaining untreated volume as: the [(pretreatment PV)–treated volume] ×0.12 ng/mL2. Conclusion A method for determining the nPSA following PGA using brachytherapy was developed. The formula relies on complete ablation of the treated volume, which resulted in no PSA contribution from that component. Other forms of ablative energy should yield similar results. Further clinical validation of this concept is warranted.